2008
DOI: 10.1143/jjap.47.4762
|View full text |Cite
|
Sign up to set email alerts
|

Helical Patterning onto Fine Pipes and Fabrication of Long Microcoils

Abstract: The helical patterning onto fine copper pipes of 80 -100 mm diameter was investigated for fabricating microcoil springs, and long microcoils of 5 mm length, 85 -100 mm pitch and with a maximum aspect ratio of 60 were obtained when the patterned specimen pipes were wet-etched. The specimen pipes were coated with a positive resist PMER P-AR900 (Tokyo Ohka Kogyo) of 2.5 -4 mm thickness, and exposed to a blue laser light beam of 473 nm wavelength. After the pipes were exposed while being scanned using a linear sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In the conventional system, [7][8][9][10][11][12][13][14][15][16] a solid blue laser (Shimadzu Solid State 473, HK5510) with a wavelength of 473 nm was used as an exposure source. The source was fixed.…”
Section: Problems In Helical Patterning Onto Fine Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…In the conventional system, [7][8][9][10][11][12][13][14][15][16] a solid blue laser (Shimadzu Solid State 473, HK5510) with a wavelength of 473 nm was used as an exposure source. The source was fixed.…”
Section: Problems In Helical Patterning Onto Fine Specimensmentioning
confidence: 99%
“…As a result, technology to form helical patterns onto wires and pipes with outer diameters of as small as 80 m was established. [10][11][12][13] In addition, the two microcoil fabrication methods mentioned above were moved to practical application. [14][15][16][17][18][19] Such MEMS microcoils are applied to coil springs used for providing appropriate contact forces in fine electrode probe pins of semiconductor device testers with large-scale integration (LSI).…”
Section: Introductionmentioning
confidence: 99%
“…To answer the requirement, various researches on developing lithography systems for replicating or delineating patterns on cylindrical materials were carried out [1][2][3][4][5][6][7]. The authors also developed laser-scan exposure systems onto fine wires and pipes with diameters of 40-500 µm [8][9][10][11][12][13]. It was demonstrated that very precise patterns were arbitrarily delineated on surfaces of such very fine cylindrical materials.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that very precise patterns were arbitrarily delineated on surfaces of such very fine cylindrical materials. In addition, fabrication processes of fine cylindrical micro-components such as coil springs and pipes with multi-holes were also developed [8][9][10][11] [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we developed a laser‐scan lithography system to form patterns on the surface of cylindrical and tubular pieces , and made possible fabrication of microcoils by etching helical patterns on copper cylinders . With microcoils fabricated by etching cylindrical pieces, thickness variation can be kept very small.…”
Section: Introductionmentioning
confidence: 99%